Transcranial static magnetic field stimulation - new non-invasive brain stimulation tool - Hikari Kirimoto; Hiroyuki Tamaki; Hideaki Onishi (Japanese Society of Physical Fitness and Sports Medicine, 2016)
Recent research has shown that the human motor cortex can be modulated by the application of static magnetic fields through the scalp. Transcranial static magnetic field stimulation (tSMS) has since received significant attention as a new non-invasive brain stimulation (NIBS) technique alongside conventional methods, such as repetitive transcranial magnetic stimulation and transcranial direct current stimulation. The advantages of the strong neodymium, iron and boron (NdFeB) magnet used in tSMS over other NIBS methods include the ease of use, absence of uncomfortable sensations for subjects, a lack of necessity for high operational skills and expensive devices, and conclusive sham stimulation allowing for controlled experiments and randomized controlled clinical trials. Hence, tSMS may be a new potential NIBS tool to modulate cerebral excitability.